SEBARAN AIR TANAH MENGGUNAKAN METODE GEOLISTRIK RESISTIVITAS KONFIGURASI DIPOLE-DIPOLE - Resma Silvia; Usman Malik (Komunikasi Fisika Indonesia, 2021)
This research has been worked in the Graha Mustamindo Permai 3 Housing area, Rimba Panjang Village, Tambang District. This research been thorough to calculate the value of measured rock resistivity in Graha Mustamindo Permai 3 Housing and analyze rock layer types through rock resistivity values at Sepakat street, Rimba Panjang, Riau. The method using in this research is geoelectric resistivity of the Dipole-dipole configuration, two lanes with the same length of 100 meters are used and spacing between electrodes is 7 meters. The data obtained were processed using Res2Dinv software version 3.54.44. The data result that obtained show two differences trajectories in Rimba Panjang Village has varying resistivity, namely in the first lane around 1.595 Ωm to 2,762 Ωm and in the second lane 1.594 Ωm to 5,879 Ωm. Groundwater potential in the first and second lanes is quite large and is thought to be in a free aquifer so that it is easy to drill.